1996
DOI: 10.1002/eji.1830260618
|View full text |Cite
|
Sign up to set email alerts
|

Immune complex‐induced interleukin‐6, interleukin‐10 and prostaglandin secretion by human monocytes: a network of pro‐ and anti‐inflammatory cytokines dependent on the antigen: antibody ratio

Abstract: We have used two experimental models of immune complexes to study the secretion of interleukin (IL)-10, IL-6 and their connection with the immune complex-induced synthesis of prostaglandin (PG) E2 by human monocytes in vitro. Immune complexes formed of tetanus toxoid and polyclonal anti-tetanus toxoid antiserum as well as heat-aggregated human serum immunoglobulins induced the release of IL-6 and IL-10 in a dose- and antigen: antibody ratio-dependent manner. Antigen-antibody complexes formed near equivalence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 20 publications
2
48
1
1
Order By: Relevance
“…PGE 2 synthesis is relied on intracellular COX including COX1 and COX2, which possess both fatty acid COX activity and PG hydroperoxidase activity. Although, IC/Ig-mediated the production of PGE 2 has been reported by several times (30,31), we were still amazed by the amount of PGE 2 by IC/Ig. Next, we demonstrated that IC/Ig induced the rapid and durative expression of COX1 and COX2 in macrophages, which may account for the reason why so large amounts of PGE 2 was induced.…”
Section: Discussionmentioning
confidence: 79%
“…PGE 2 synthesis is relied on intracellular COX including COX1 and COX2, which possess both fatty acid COX activity and PG hydroperoxidase activity. Although, IC/Ig-mediated the production of PGE 2 has been reported by several times (30,31), we were still amazed by the amount of PGE 2 by IC/Ig. Next, we demonstrated that IC/Ig induced the rapid and durative expression of COX1 and COX2 in macrophages, which may account for the reason why so large amounts of PGE 2 was induced.…”
Section: Discussionmentioning
confidence: 79%
“…An induction of IL-10 might be anticipated in active SLE because immune complexes [31,43] as well as apoptotic cells [32,33] can cause IL-10 production in human PBMC in vitro. However, in the present study we failed to detect as determined by immunoassay, significant levels of IL-10 produced by PBMC stimulated by the combination of apoptotic U937 cells and SLE-Igb.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that immune complexes can induce IL-10 production [31]. Furthermore apoptotic cells can produce IL-10 [32,33] as well as promote production of IL-10 in PBMC [34].…”
Section: Possible Production Of Il-10 Induced By Apoptotic U937 Cellsmentioning
confidence: 99%
“…Given the potent anti-inflammatory role of IL-10, it is possible that the decreased survival we observed in the antibody-treated IL-10 Ϫ/Ϫ mice resulted from increased inflammation induced by immune complexes formed when the exogenous antibody to GXM was administered. Immune complexes induce the release of many proinflammatory cytokines such as IL-1␤, IL-6, and TNF-␣, as well as IL-10 and vasoactive substances such as platelet-activating factor (3,4,74). In the absence of the inhibition of inflammation that is usually caused by IL-10, these mediators may act unopposed, thereby causing intense inflammatory damage to the host.…”
Section: Discussionmentioning
confidence: 99%